PENGARUH PEMANFAATAN WAKTU LUANG, INTENSITAS INTERAKSI GURU DAN KELUARGA TERHADAP PRESTASI BELAJAR SISWA - -, Wahyono -; -, Rispantyo - (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2012)
ABSTRACT This study aims to analyze the significance of the effect of the use of leisure time, the intensity of the interaction of the teacher, and the intensity of family interaction on student achievement at SMK Negeri 2 Surakarta. The research data were taken through a questionnaire as much as 258 students. Data analysis tool that is used by multiple linear regression analysis, t test, F test, and Adjusted R2. Based on t-test is known that there is a significant effect of the partial intensity of family interaction on learning achievement, and there is no significant effect between the use of leisure time and the intensity of the interaction of teachers on student achievement XI SMK Negeri 2 Surakarta. Based on the F test indicates that there is significant influence between variables simultaneous utilization of spare time, the intensity of the interaction of teachers and parents on student achievement XI SMK Negeri 2 Surakarta. Keywords: Use of Free Time, Interaction Intensity Teacher, Family, Learning Achievement.